BASE STATION MONITORING TECHNOLOGIES AND BEST PRACTICES - Ibrokhimkhuja Rikhsikhujaev Khurshidkhuja ugli (The latest news and research in education, 2025)
This article explores the significance of base station monitoring technologies and the best practices for ensuring stable telecommunication network performance. It provides an in-depth analysis of monitoring components, including sensors, remote management systems, and software platforms, which collectively ensure the reliability and security of communication infrastructure. The paper discusses modern innovations such as IoT-based monitoring, Artificial Intelligence (AI), cloud computing, and edge technologies that enable predictive maintenance and real-time network optimization. Furthermore, it highlights common challenges and future trends, emphasizing the importance of cybersecurity, energy efficiency, and automation in maintaining continuous service quality.